The value of equal access to mandatory disclosure: evidence from the Great Postal Strike of 1970 - Li, Bin; Venkatachalam, Mohan (Review of Accounting Studies, 2025)
Abstract How important is equal access to mandatory disclosures? We exploit the postal strike of 1970 that caused a delay in the delivery of annual reports via mail. This strike created unequal access because certain investors (e.g., institutions) had both the incentives and ability to obtain the annual reports by other means. Theory predicts that, when differential access exists, adverse selection problems intensify, causing a decline in stock trading. Our findings support this prediction: stock trading volume decreased by approximately 28% for firms unable to deliver the annual reports to shareholders during the strike, and this trading decline gradually dissipated afterward. Further tests confirm adverse selection as the primary mechanism. Overall, our paper underscores the importance of equal access to annual reports—a key mandated disclosure—and demonstrates the value of these reports to shareholders, as evidenced by their reluctance to trade absent this information.